Evaluation of Glucose, AST, ALT, Urea and Albumin Parameters in Children with Rotavirus Diagnosis - Tahiroğlu, Veysel; Öztürk, Cihat (My University, 2023)
Aim: This study aims to evaluate glucose, AST, ALT, urea and albumin parameters in patients diagnosed with rotavirus. Materials and Methods: Children who applied to Şırnak State Hospital Pediatrics Polyclinics (6 months to 18 years of age), whose fecal samples were sent to the laboratory by the pediatrician considering the diagnosis of rotavirus, and whose microbiological examinations were confirmed by immunochromatographic methods (6 months to 18 years), were included in the study by scanning the system. Results: When the mean ages of glucose, ALT, AST, urea, and albumin data of the rotavirus negative group were evaluated, they were found to be 1.82±2.66, 1.77±2.72, 1.76±2.72, 1.69±2.68, 1.87±2.88, respectively. and in rotavirus positives, respectively; It was found to be 1.16±1.35, 1.09±1.31, 1.09±1.31, 1.10±1.32, 1.11±1.30. While the median values of glucose, AST, ALT, urea and albumin in rotavirus negatives were 84 mg/dl, 36 U/L, 19 U/L, 14 mg/dL, 3.79 g/dL, respectively, the median values in rotavirus positives were 75 mg, respectively. /dL, 45 U/L, 26 U/L, 18 mg/dL, 3.98 g/dL were detected. All parameters were statistically significant (p
Keywords: Albumin; Rotavirus; AST; Urea; Glucose; ALT